PEMBERDAYAAN MASYARAKAT DESA BATURONO KECAMATAN SALAM KABUPATEN MAGELANG MELALUI PEN4EMBANGAN PERTANIAN ORGANIK - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Some farmers in Baturono Village,Magelang District had shifted their farming practice to organic method. Oneform of the organic farming practice in rice cultivation is the System of Rice Intensification (SRI).However, the farmers still faced some problems related to organic fertilizer and pesticide, water management, equipments, as well as post-harvest technique. This activity aimed to facilitate farmers in Baturono Villageto become organicfarmers. Inthe same time, it can raise awareness and empathy of students as well as to develop a discourse of interdisciplinaryactivities. In addition, this activity would bring up the input for the UGM to develop research programs and community services. During the activities, the planned programs had been completed, which can be categorized into organic fertilizers, organic pesticides, SRIrice-cultivation.method, post-harvest, and others groups.